Kapasitas Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) dalam Rekrutmen PPPK di Kabupaten Pesisir Selatan - Hilda Desma Fitri; Yulia Hanoselina (YASIN, 2026)
The recruitment of Government Employees with Work Agreements (Pegawai Pemerintah dengan Perjanjian Kerja, PPPK) is one of the government’s strategic instruments for meeting the needs of professional and competent civil servants (Aparatur Sipil Negara, ASN) within local governments; however, in practice it still faces various challenges in terms of planning, coordination, and the ability to adapt to regulatory changes and digital systems. This study aims to analyze the capacity of the Regional Personnel and Human Resources Development Agency (Badan Kepegawaian dan Pengembangan Sumber Daya Manusia, BKPSDM) of Pesisir Selatan Regency in the PPPK recruitment process by using Duncan’s organizational effectiveness theory as presented in Steers, which includes the dimensions of goal attainment, integration, and adaptation. The research employed a qualitative method with a descriptive approach, with data collected through in-depth interviews with key informants and document studies related to the PPPK recruitment process. The findings show that BKPSDM’s capacity in PPPK recruitment is relatively effective; the dimensions of goal attainment and integration have functioned fairly well, as reflected in ASN workforce planning based on Job Analysis and Workload Analysis, transparent selection implementation through the Computer Assisted Test (CAT) system, and intensive coordination with central agencies and local government units. However, in the adaptation dimension, several constraints remain, including limited regional budgets, human resource readiness, inadequate facilities and infrastructure, and dependence on national systems that are frequently subject to change. The study concludes that PPPK recruitment in Pesisir Selatan Regency has not yet been fully optimal and that strengthening the organization’s adaptive capacity is required to maintain the effectiveness of PPPK recruitment on a sustainable basis.